KAJIAN TENTANG PENETAPAN TARGET RETRIBUSI PARKIR DI KOTA SEMARANG - Ihwanudin, Rizka; ., Yuwanto; Widayati, Wiwik (Journal of Politic and Government Studies, 2014)
with its supporting and inhibiting factors. The parking levy in Semarang City has considerable potential.The number of vehicles in Semarang City on 2010, there were 1.086.890 motor vehicles consisting of 907.303two-wheeled vehicles/motorcycles and 179.517 four-wheeled vehicles. Based on Regional Regulations No. 2and 3 in 2012 for public roadside parking, Semarang City Government collect fees of Rp 1.000 for a twowheeledvehicle and Rp 2.000 for a four-wheeled vehicle. But Semarang City Government has set a target ofsectors parking levy are relatively small in number.In order to explain the process of target setting of the parking levy in Semarang City, then usedqualitative research methods. Subjects in this study were Dishubkominfo Semarang City and Commision BDPRD Semarang. The method of data collection was through interviews, observation, and examined relevantdocuments to this study to support the completeness of the information needed.The result shows that process of target setting of the parking levy in Semarang City is Dishubkominfodraft targets parking levy. The draft was given to DPKAD to be processed along with the draft revenue andother expenditures. After that the draft of the target parking levy that have become RAPBD submitted to DPRDSemarang for approval. In this case, Commission B DPRD Semarang who will evaluate the target parking levyfrom Dishubkominfo. Withdrawal system in Semarang city parking levy this year are managed entirely byDishubkominfo. Dishubkominfo have formulas for calculating the potential of parking, the number of parkingspot x workday x 12 months x average payment per parking spot.To simplify the process of target setting of the parking levy, Dishubkominfo and DPRD need to becoordinated in the calculation of the potential of parking in the city of Semarang. Constraints in the parking levywithdrawal method which is managed by Dishubkominfo can be overcome by adding personnel and morefirmly to the parking attendants who violate the rules.Keywords : target setting process, parking levy